Privacy-Preserving Techniques for Social Network Analysis - Mendonça, André L. C.; Brito, Felipe T.; Machado, Javam C. (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2023: Anais Estendidos do XXXVIII Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2023.25632, 2023)
With the increasing concerns over data privacy, preserving the privacy of individuals in social network analysis has become crucial. This tutorial provides a comprehensive overview of methods and techniques to protect individual privacy while conducting social network analysis. We perform a deep analysis of differential privacy, which is a rigorous mathematical framework to protect individual privacy while enabling accurate analysis of network structure and characteristics. Additionally, this tutorial explores a variety of examples and case studies to demonstrate the application of these techniques in practical scenarios.